Synthesis and Applications of Functionalized Magnetic Nanomaterials in Enantioseparation. Issue 1 (2nd January 2019) - Deng, Xiaojuan; Li, Wenbin; Ding, Guosheng; Xue, Tao; Chen, Xiaoping
Abstract : Efficient enantioselective separation is a challenging task due to the identical physical and chemical properties of enantiomers. Functionalized magnetic nanomaterials modified with chiral ligands on their surface possess both magnetic property and chiral recognition ability, and have demonstrated great potential in chiral discrimination. This review summarizes the applications of magnetic nanomaterials modified with various chiral selectors (e.g., β -cyclodextrins, polymers, proteins, amino acids and cellulose) in enantioselective separation. After proper preparation and modification, these functionalized magnetic nanomaterials are effective for enantioseparation. Therefore, enantioseparations based on functionalized magnetic nanomaterials are convenient, economical and effective.